Labor Regime of Artists - Pasco Cosmópolis, Mario (1974)
The article provides a detailed analysis of the labor regime for artists, highlighting the specific legislation aimed at protecting their rights and benefits in Peru, represented by Decree Law 19479 and Regulatory Supreme Decree No. 010-73-TR. This legislation seeks to adapt the principles of Labor Law to the particularities and demands of the artistic sector. In this regard, the author recognizes the importance of establishing a specific legal treatment for the sector as they are considered special workers with unique needs and characteristics. Along these lines, the article addresses key aspects such as the personal scope of artists, employment contracts, exclusivity, limitations for foreign artists, and the obligations of their employers. These obligations include, among other things, registration with the Artists' Social Rights Fund, drafting written contracts, and registration with the Municipal Council. When presenting the legal framework, the author emphasizes that the law seeks to adapt the principles of Labor Law to the particularities and demands of the artistic sector, to provide them with a specific legal framework that addresses their unique characteristics. This is to ensure the protection of their labor rights and guarantee social security for this sector within a specific regulatory framework.